2020
DOI: 10.21203/rs.3.rs-52746/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explaining Factors Affecting Help-Seeking Behaviors in Women with Urinary Incontinence: A Qualitative Study

Abstract: Background: Urinary incontinence is widely accepted to be among the most important issues in the global health system. However, only a limited number of women refer for treatment as different factors make help-seeking behaviors more complicated than they initially seem to be. The aim of this study was to explain the factors affecting help-seeking behaviors in women suffering from urinary incontinence.Methods: The present study used a qualitative method, the conventional content analysis approach. The study was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…According to studies, < 30% of women seek the help of healthcare professionals [ 16 , 17 ]. Previous researchers have revealed that several reasons for women not seeking professional treatment include stigma and embarrassment, the lack of knowledge about PFD, the high cost of treatment, excessive wait times, limited access to health care services, and concerns about perceived consequences, which hinder the implementation of pelvic floor rehabilitation and are detrimental to individual health and quality of life [ 18 , 19 ]. As a result, developing innovative strategies or modalities of pelvic floor management for women with or at risk of PFD is critical.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies, < 30% of women seek the help of healthcare professionals [ 16 , 17 ]. Previous researchers have revealed that several reasons for women not seeking professional treatment include stigma and embarrassment, the lack of knowledge about PFD, the high cost of treatment, excessive wait times, limited access to health care services, and concerns about perceived consequences, which hinder the implementation of pelvic floor rehabilitation and are detrimental to individual health and quality of life [ 18 , 19 ]. As a result, developing innovative strategies or modalities of pelvic floor management for women with or at risk of PFD is critical.…”
Section: Introductionmentioning
confidence: 99%